Investigating the Introduction of Fuel Cell Technology in Underground Mining Equipment - Mokgethi, Lesego (University of the Witwatersrand, Johannesburg, 2025)
Fossil fuels, which are major energy sources, have harmful effects on the environment, and their continued use contributes to global warming and climate change. Moreover, diesel combustible engines in underground mining machinery emit noise, diesel exhausts, and heat during operation, creating an unfavourable working environment. Diesel particulate matter has been classified as a human carcinogen, and occupational exposure limits have already been established in other countries and are anticipated in South Africa. The research investigated the introduction of hydrogen fuel cell technology in underground machinery, particularly the diesel load haul dump machine, to mitigate harmful emissions during their operation and promote the use of renewable energy. The objectives of the study entailed assessing the effects of diesel exhausts in underground working environment, as well as actions taken to reduce emissions. The study also looked at the key aspects that need to be considered to support the application of fuel cell technology in mining operations, constraints affecting their adoption and status of existing regulations and policies. The application of hydrogen fuel cell technology in the mining industry would promote the beneficiation of platinum and other minerals in South Africa, further contributing to economic development and growth. The successful implementation of hydrogen fuel cell technology would also result in a healthier working environment for underground employees and would be a step towards achieving a carbon-free environment. The study employed a mixed-method approach. Data was collected through semi- structured interviews conducted with relevant subject matter experts within the mining industry. Measurements of the operating environment were taken, and the maintenance requirements of the current internal combustible engines and site visits to different sections of the case study mine were conducted. Diesel fuelled machines have harmful effects on the working environment and contribute to global warming. Measures put in place to reduce effects of diesel exhausts affect productivity and are mostly human dependent such as effective use of personal protective equipment. During the design stage, key considerations iv such as the environment, performance and emissions requirements must be studied. Prior to implementing fuel cell technology in underground mining equipment, sufficient testing must be done to ensure reliability and reduce repair costs. To ensure the smooth implementation of Hydrogen Fuel Cell (HFC) in underground equipment, adequate assessment of the skills and training will be required. Existing regulations and policies must be reviewed, and new policies must be introduced to support hydrogen fuel cell technology and to increase investment in the South African hydrogen economy. With the worldview shifting towards a sustainable environment and development, all research and development that supports renewable energy is critical. Research and development to reduce capital costs of HFC technology through improved processes and large-scale production must be done.
A research report submitted in fulfillment of the requirements for the Master of Science, in the Faculty of Engineering and the Built Environment, School of Mining Engineering , University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Greenhouse Gas Emissions; Renewable Energy; Hydrogen Economy; Fuel Cell Technology; Diesel Exhausts Emissions; SDG-7: Affordable and clean energy; SDG-13: Climate action